Maximizing the impact of exposure to scientific role models: Testing an intervention to increase science identity among adolescent girls. Issue 7 (27th April 2021) - Merritt, Sally K.; Hitti, Aline; Van Camp, Amanda R.; Shaffer, Emily; Sanchez, Michelle H.; O'Brien, Laurie T.
Abstract: A field experiment tested an intervention to maximize the impact of a science outreach program by encouraging early adolescent girls ( N = 240, Mage =12) to adopt female role models. Girls participated in workshops led by female role models who were scientific experts in their field. Afterward, they were randomly assigned to choose and write about their favorite workshop leader or to write about the first workshop leader. We hypothesized that the intervention would benefit girls who chose and wrote about a favorite leader. However, girls in both conditions experienced significant increases in science identity. Girls demonstrated strong role model identification with the workshop leaders; moreover, role model identification was associated with increases in science identity. Girls in the chosen leader condition focused on her competence and supportiveness more than girls in the assigned leader condition. There was no difference in science identity between girls from well‐represented and underrepresented minority (URM) ethnic groups in scientific fields. URM girls, surprisingly, identified more with the workshop leader than well‐represented girls. Science workshops led by female role models with relevant expertise may facilitate science identification among early adolescent girls from diverse ethnic backgrounds.